2022
DOI: 10.3389/fchem.2022.1089708
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and perspectives of CeO2-based catalysts: Electronic properties and applications for energy storage and conversion

Abstract: Cerium dioxide (CeO2, ceria) has long been regarded as one of the key materials in modern catalysis, both as a support and as a catalyst itself. Apart from its well-established use (three-way catalysts and diesel engines), CeO2 has been widely used as a cocatalyst/catalyst in energy conversion and storage applications. The importance stems from the oxygen storage capacity of ceria, which allows it to release oxygen under reducing conditions and to store oxygen by filling oxygen vacancies under oxidizing condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…CeO 2 is known for its unique redox chemistry. Oxidation states +3 and +4 steadily exist and can easily switch between each other [57,58]. Therefore, Ce 4+ -620 • C was investigated by STEM-EELS measurements to determine the cerium valence, at a nanoparticle and at a region of a nanoribbon without a particle.…”
Section: Determination Of Cerium Oxidation State and The Ratio Betwee...mentioning
confidence: 99%
“…CeO 2 is known for its unique redox chemistry. Oxidation states +3 and +4 steadily exist and can easily switch between each other [57,58]. Therefore, Ce 4+ -620 • C was investigated by STEM-EELS measurements to determine the cerium valence, at a nanoparticle and at a region of a nanoribbon without a particle.…”
Section: Determination Of Cerium Oxidation State and The Ratio Betwee...mentioning
confidence: 99%
“…Synthesis of metal oxide nanoparticles with characteristic sizes, tailored structure and morphology is an important aspect in the development of novel nanomaterials with enhanced properties, manufacturing of new nanostructures and investigating their applications. Cerium oxide nanostructures were globally obtained due to their excellent properties with potential applications in energy conversion and storage, catalysis cosmetic product solar cells, mechanical polishing, automotive exhaust treatments, the biomedical field and gas sensor therapeutic agents [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The unique properties of cerium oxide derive from its stable fluorite-type structure and the coexistence of the two (Ce 3+ and Ce 4+ ) oxidation states which can be switched to each other depending on the local environmental conditions [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facile redox interconversion between the two oxidation states of the cerium ion is responsible for many of ceria's promising properties. 27 It was recently shown that visible excitation of gold nanoparticles embedded in a cerium oxide thin film grown by molecular beam epitaxy results in efficient electron injection as judged by the detection of electron small polarons in the metal oxide. 13 T h i s c o n t e n t i s The photocatalytic reactivity of metal/semiconductor nanostructures can be improved by surface hybridization with graphene due to its high electron conductivity and high surface area.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A powerful strategy for photocatalysis pairs a metal oxide semiconductor with a plasmonic metal NP. ,,, Among the metal oxide semiconductor materials, CeO 2 (ceria) has attracted much attention as an SPR acceptor material for photocatalysis. ,,, Electron occupation of the 4f band reduces Ce 4+ centers to Ce 3+ . Under reducing conditions, an oxygen atom is removed from its lattice position, leaving behind two electrons that localize in the 4f states of two nearby cerium atoms. Facile redox interconversion between the two oxidation states of the cerium ion is responsible for many of ceria’s promising properties . It was recently shown that visible excitation of gold nanoparticles embedded in a cerium oxide thin film grown by molecular beam epitaxy results in efficient electron injection as judged by the detection of electron small polarons in the metal oxide …”
Section: Introductionmentioning
confidence: 99%